Research of the Modeling Method of Damaged Helical Gear Remanufacturing based on Local Point Cloud Data - Xiaoling Wei; Yi Meng; Xiujun Sun (Jixie chuandong)
Abstract Aiming at the problems of high data repeatability, low utilization rate and low construction accuracy of the damaged part model in the remanufacturing process of helical gear parts, a modeling method for constructing a complete part model using local area point cloud data is proposed. Using the local area point cloud data, the complete intact gear part model with the characteristics of the helical gear itself is built. Meanwhile, the damage tooth region model is constructed separately, and the high-precision damage gear model is obtained by model splicing. The coordinate model of the intact gear model and the damage gear model are used for registration to obtain the damage amount model. Finally, through the practice case, the proposed method is verified.